Revision of the Llandovery (lower Silurian) trimerellide brachiopod Yidurella in South China - Chen, Di; Candela, Yves; Huang, Bing (Palaeoworld, 2023)
Although a minor group of brachiopods in the Ordovician and Silurian, the trimerellides include some of the largest known brachiopods in the Early Paleozoic. Yidurella Zeng, a monospecific genus of moderate size from the Shamao Formation of Tizikou, Yidu City, Hubei Province, was originally described as having a solid platform. However, new material collected from the type locality (Tizikou Section), the Kapeng Reservoir Section in Hunan Province, and from the Yangjiawanzi and Hongyan sections in Yunnan Province reveal that its platform is vaulted. A new, emended diagnosis is therefore proposed for Yidurella. All specimens of Yidurella studied were collected from a single thin layer in Telychian rocks between the Lower Red Beds and the Upper Red Beds, suggesting its potential for biostratigraphic correlation. Associated rhynchonelliform brachiopods and corals in each section, together with a population analysis of Yidurella yiduensis Zeng from the Kapeng Reservoir Section, indicate that this trimerellide inhabited in inner to outer shelf environments (Benthic Assemblages (BA) 2 to 3) in warm water. The genus is also tentatively recognized in contemporaneous rocks from Severnaya Zemlya in Russia.